Study of plant remains from a fluvial shellmound (Monte Castelo, RO, Brazil) using the X-ray MicroCT imaging technique. (August 2019) - Calo, Cristina Marilin; Rizzutto, Marcia A.; Watling, Jennifer; Furquim, Laura; Shock, Myrtle P.; Andrello, Avacir C.; Appoloni, Carlos R.; Freitas, Fabio O.; Kistler, Logan; Zimpel, Carlos A.; Hermenegildo, Tiago; Neves, Eduardo G.; et al.
Abstract: This work applies the X-ray MicroCT imaging technique to discuss the identification and preservation/disturbance conditions of plant remains from the Monte Castelo archaeological site, in Brazil's southwestern Amazonia. A preliminary hypothesis based on external morphological traits and the presence of typical starch grains, associates these materials to the Poaceae caryopsis. Moreover, based on their well-preserved non-charred aspect, mineralization was considered as a possible in-situ preservation process. Data from the X-ray computed microtomography (MicroCT) analysis showed that the internal anatomy of the samples corresponds to another type of fruit, described as a small drupe sharing characters with some Anacardiaceae fruits. Additionally, all studied specimens contain a number of exogenous organic and inorganic elements suggesting the action of some disturbance processes on the Monte Castelo plant material. Highlights: X-ray MicroCT is a suitable complementary technique to archaeobotanical studies. The internal morphology of Monte Castelo samples is consistent with drupes. Biomineralizations and others mineral particles into the samples were distinguished. In-situ preservation of samples could not be attributed to a mineralization process.